2(y+2)=3y-4

Simple and best practice solution for 2(y+2)=3y-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y+2)=3y-4 equation:


Simplifying
2(y + 2) = 3y + -4

Reorder the terms:
2(2 + y) = 3y + -4
(2 * 2 + y * 2) = 3y + -4
(4 + 2y) = 3y + -4

Reorder the terms:
4 + 2y = -4 + 3y

Solving
4 + 2y = -4 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
4 + 2y + -3y = -4 + 3y + -3y

Combine like terms: 2y + -3y = -1y
4 + -1y = -4 + 3y + -3y

Combine like terms: 3y + -3y = 0
4 + -1y = -4 + 0
4 + -1y = -4

Add '-4' to each side of the equation.
4 + -4 + -1y = -4 + -4

Combine like terms: 4 + -4 = 0
0 + -1y = -4 + -4
-1y = -4 + -4

Combine like terms: -4 + -4 = -8
-1y = -8

Divide each side by '-1'.
y = 8

Simplifying
y = 8

See similar equations:

| 2w+5x-11y+6w=9x+6y | | 2w+5x-11y+6w=9x-6y | | 4x+3(1+2x)=73 | | 7-2x=-5 | | 1+4x=29 | | v+8=2 | | 4t-4=16 | | 8ef+5ef-ef= | | xy=6-x | | 6x+18=13x-45 | | 0.012x^2-0.583x+35.727=55 | | -3(4)+9=-57 | | 846=n-37 | | 11-2x=8-5x | | 2(2x+60)+2(5x)=360 | | w-9w=73-89 | | 11-18x-8x^2= | | 0.5d-0.75=0.6d | | log(0.8x+1)=log(0.8y+1)-log(1-u) | | 5x-18*4=36 | | 4z=28-0.25(4-16z) | | ln(0.8x+1)=ln(0.8y+1)-ln(1-u) | | 7-6x=4x-23 | | x^4-28x-288=0 | | 7-7x=37-14x | | 4y-2=12x | | 5y^2-14y+8=0 | | 1.5y+4=-15 | | 3x+9=51-9x | | -4c=-8 | | 7.9z-1.5=30.1 | | 5(2z-1)-4(z+4)=4(z+1) |

Equations solver categories